1975
DOI: 10.1111/j.1752-1688.1975.tb00683.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE EVALUATION OF THREE URBAN RUNOFF MODELS1

Abstract: Three urban runoff models, namely, the Road Research Laboratory Model (RRLM), the Storm Water Management Model (SWMM) and the University of Cincinnati Urban Runoff Model (UCURM), were examined by comparing the model simulated hydrographs with the hydrographs measured on several instrumented urban watersheds. This comparison was done for the hydrograph peak points as well as for the entire hydrographs using such statistical measures as the correlation coefficient, the special correlation coefficient and the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Compared with other models, SWMM has a better simulation effect [38], and it has been widely used in the evaluation and forecasting of the surface runoff process of storm floods by relevant scholars. Marsalek et al [33] conducted in-depth studies on 12 storm events in three typical small watersheds in the United States and found that the SWMM simulation results fit well with the measured runoff results. Daeryong et al [34] established a SWMM model for Ulsan, Korea, and analyzed the required scales and storage ranges of three types of storage ponds (with return periods of 2 years, 10 years, and 100 years).…”
Section: Hydrological Model Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other models, SWMM has a better simulation effect [38], and it has been widely used in the evaluation and forecasting of the surface runoff process of storm floods by relevant scholars. Marsalek et al [33] conducted in-depth studies on 12 storm events in three typical small watersheds in the United States and found that the SWMM simulation results fit well with the measured runoff results. Daeryong et al [34] established a SWMM model for Ulsan, Korea, and analyzed the required scales and storage ranges of three types of storage ponds (with return periods of 2 years, 10 years, and 100 years).…”
Section: Hydrological Model Selectionmentioning
confidence: 99%
“…The relevant models include the Long-Term Hydrologic Impact Assessment-Low Impact Development (L-THIA-LID) model [29]; the improved SCS-CN model [30,31]; the System for Urban Storm-water Treatment and Analysis Integration (SUSTAIN) model [32]; and the SWMM [21,[33][34][35]. In 2016, DHI-China developed the Sponge City Aided Design (SCAD) module and added it to the Mike Urban model directed against the requirements of the Chinese market [36].…”
Section: Hydrological Model Selectionmentioning
confidence: 99%
“…For example, hydrographs presented by Jolly (1973) give values of 4-8 h for snowmelt and 1.5-10 h for rain-on-snow, while times of rise of 7-13 h were derived from snowmelt hydrographs for a large (109 km 2 ) basin in Topeka, Kansas (Pope & Bevans, 1986). The Kawartha Heights time of rise values are intermediate between Bengtsson's (1985) observations for snowmelt (10-12 h) and rainfall (18-24 h) in a rural catchment, and the shorter values (0.18-4.8 h) reported by Marsalek et al (1975) for rainfall inputs to small urban basins. This suggests that travel times during snowmelt and rain-on-snow may be reduced as a result of the increased drainage efficiency that accompanies suburban development.…”
Section: Yearmentioning
confidence: 89%
“…The top hydrograph also shows that positive and negative differences do not cancel each other out to give a perfect ISE value of zero. Marsalek et al (1975) examined three urban runoff models, namely the Road Research Laboratory Model (RRLM), the Storm Water Management Model (SWMM), and the University of Cincinnati Urban Runoff Model (UCURM), by comparing the modeled and observed hydrographs on several urban watersheds. This comparison was done for the hydrograph peak points as well as for the entire hydrographs using such statistical measures as the correlation coefficient, the special correlation coefficient and the integral square error.…”
Section: Integral Square Errormentioning
confidence: 99%